TEACHING FACTORY LEARNING MANAGEMENT IN DEVELOPING ENTREPRENEURIAL SPIRIT IN STUDENTS: THE STUDY OF SMK MUHAMMADIYAH GAMPING YOGYAKARTA - Antony, Rian; Subari, Adrianus Junaidi; Mulyatno, Carolus Borromeus (Jurnal Inovasi Pendidikan dan Teknologi Informasi (JIPTI), 2023)
Teaching factory learning plays a significant role in fostering an entrepreneurial spirit, which is the process of developing and implementing creativity and innovations to improve the economy. This research aims to determine the management of teaching factory learning in developing the students' entrepreneurial spirit at SMK Muhammadiyah Gamping. This research is descriptive qualitative research. The research method applied is a case study method with data collection through in-depth interviews. The research results show that the teaching factory learning management has been running well—as can be seen from the optimal functioning of each management function. However, it is necessary to develop more specific teaching factory learning to be competent to provide a more tangible picture for each student, especially in developing an entrepreneurial spirit. With this research, an overview of implementing the teaching factory learning practice that is appropriate, correct, and effective can be discovered in more depth.